An infrared sensor analysing label‐free the secondary structure of the Abeta peptide in presence of complex fluids. Issue 3 (23rd March 2015) - Nabers, Andreas; Ollesch, Julian; Schartner, Jonas; Kötting, Carsten; Genius, Just; Haußmann, Ute; Klafki, Hans; Wiltfang, Jens; Gerwert, Klaus
Abstract : The secondary structure change of the Abeta peptide to beta‐sheet was proposed as an early event in Alzheimer's disease. The transition may be used for diagnostics of this disease in an early state. We present an Attenuated Total Reflection (ATR) sensor modified with a specific antibody to extract minute amounts of Abeta peptide out of a complex fluid. Thereby, the Abeta peptide secondary structure was determined in its physiological aqueous environment by FTIR‐difference‐spectroscopy. The presented results open the door for label‐free Alzheimer diagnostics in cerebrospinal fluid or blood. It can be extended to further neurodegenerative diseases.An immunologic ATR‐FTIR sensor for Abeta peptide secondary structure analysis in complex fluids is presented. Abstract : An Attenuated Total Reflection (ATR) sensor modified with a specific antibody to extract minute amounts of Abeta peptide out of a complex fluid is presented. The Abeta peptide secondary structure was determined in its physiological aqueous environment by FTIR‐difference‐spectroscopy. The presented results open the door for label‐free Alzheimer diagnostics in cerebrospinal fluid or blood. It can be extended to further neurodegenerative diseases.